Game theory in conjuction with a digitized information retrieval unit - Andalis, Arthur B.; Jamin, Raymond P. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Game theory is a distinct and interdisciplinary approach to the study of human behavior. The disciplines most involved in game theory are mathematics, economics and the other social and behavioral science. This study aimed to propose the implementation of Game Theory in Information System using the on-line public access catalog (OPAC)The objectives of the study are the following: 1) to determine if there is a connection between categories and data; 2) to prove if the case being studied useful as a conceptual explanation for the process of implementation itself; 3) to know if the theory provide a relevant explanation of actual problems that present itself in consistency while at the same time being consistent with the actual and basic problems presented; 4) to determine if the theory can be modified as conditions change as well as variations of availability of future data ; 5) to determine if the theory present a conceptualization of process, action, and or interaction; and 6) to determine if there is an evident central phenomenon that can be applicable to any theoretical models.
The series of data comparison were presented through theoretical sampling. The study sought diversity in the collective data, and it also seek a distinct relationship between them. The study gauge the emerging theory against the collective data involved, to further scrutinize and prove the hypothesis. The tool that used in this study is Grounded theory and methodology.
The study concludes that there is a need for creating a guideline to further revolutionize the Information system. Game theory would aid significantly in providing a strategic and highly efficient Information Retrieval unit. Studies direct the game theory is possible in any most likely field present. The strategy of implementing a more thorough application of game theory will result to a more successful and less frustrating search results. It is but a simple analogy of preference.
The study recommends the following: 1) further re-evaluation of OPAC and its relevance to the continuing progress of the Information System; 2) further revisions for the software producers to utilize the importance of game theory in the development of a new breed of strategic Information retrieval systems; 3) the creation of future guidelines necessitates the presence.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Game theory -- Computer programs